Forbs, grasses, and grassland fire behaviour. (16th April 2018) - Wragg, Peter D.; Mielke, Troy; Tilman, David
Abstract: In grasslands and savannas, fire regime—frequently a major determinant of woody encroachment, herbaceous species composition and diversity, and nutrient cycling—is influenced by the quantity and characteristics of plant fuel. Laboratory studies reveal variation in flammability among herbaceous species, but field experiments are needed to assess whether herbaceous species composition meaningfully affects ecosystem‐scale fire behaviour. In our North American tallgrass prairie study system, grasses' thinner leaves and longer leaf retention appeared to create a finer, more aerated, more connected fuel bed than forbs. We tested the hypothesis that grasses promote fire spread area, fire intensity, and associated facets of fire behaviour more strongly than an equivalent mass of forbs. We characterized spring fires over multiple years in 315 annually ignited plots spanning profound gradients of plant biomass, cover, and grass:forb ratio that resulted from species richness and composition treatments, in a 20‐year grassland biodiversity experiment. Grasses increased fire spread and associated facets of fire behaviour, compared with an equivalent biomass or cover of forbs. Grass dominance increased fire spread area—or equivalently increased fire frequency at any given point. For fire to spread through 50% of the 9 m × 9 m plot area required approximately twice as high an abundance of forbs as of grasses. Grass dominance also resulted in fires that advanced faster, were more intense (higher rates of heat release per unit fireline length), caused more damage to plants, and released heat to greater heights. Fire temperature at 50 cm above‐ground was about twice as high in plots with only grasses as in plots with the same biomass of forbs. Synthesis . Even within herbaceous ecosystems that may appear homogenously flammable compared with less flammable woody ecosystems, fuel quality—specifically, the proportional abundance of grasses—combines with fuel quantity and ignitions to determine effective fire regime at a given point. In spring burns, grass‐dominated plots burn more completely and generate higher temperatures, and thus better suppress woody plants and volatilize more nutrients, than forb‐dominated plots (holding all else equal). Abstract : Even within herbaceous ecosystems, fuel quality—specifically, the proportional abundance of grasses vs. forbs—combines with fuel quantity and ignitions to determine effective fire regime at a given point. In spring burns, grass‐dominated plots burn more completely and generate higher temperatures, and thus better suppress woody plants and volatilize more nutrients, than forb‐dominated plots.